Influence of mineral fertilizers for nourishing mode of soil at growing of spring wheat - Шевніков, Д. М. (Scientific Progress & Innovations, 2012)
Using of mineral fertilizers, especially nitric, in moderate doses (N23-45) in combination with phosphoric and potassium allows to improve the nourishing mode of soil. Supply plants by nourishing elements as a result of mineralization of organic compounds by the ground microorganisms and by a transition mineral heavily soluble substance in soluble. It forwards more favourable terms for growth and development of plants and maintenance of fertility of soil at high level. The redistribution of nitrate and ammoniac forms of nitrogen took place in the end of vegetation of spring wheat.